2014
DOI: 10.1002/ijc.29231
|View full text |Cite
|
Sign up to set email alerts
|

CAST: A retrospective analysis of cabazitaxel and abiraterone acetate sequential treatment in patients with metastatic castrate‐resistant prostate cancer previously treated with docetaxel

Abstract: Cabazitaxel and abiraterone have both received approval for treating metastatic castrate‐resistant prostate cancer (mCRPC) patients after first‐line docetaxel therapy. In the cabazitaxel and abiraterone sequential treatment (CAST) study, the clinical outcome of docetaxel‐treated mCRPC patients treated sequentially with both cabazitaxel and abiraterone was studied. Data were collected retrospectively from mCRPC patients at 12 hospitals across the Netherlands who initiated cabazitaxel and/or abiraterone before D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
2

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 24 publications
1
29
0
2
Order By: Relevance
“…Specifically, despite the limitations of non-randomized retrospective studies, the CAST [17] report was the first to investigate the outcomes of C followed by abiraterone acetate and vice versa in two groups of patients following progression while on D. In this study, the activity of C as a third-line therapy was found to be inferior compared with its use as a second-line therapy in the other group. It is likely that the presence of constitutively activated androgen receptor splice variants, which generally lack the carboxy-terminal ligand-binding domain, resulted in resistance to abiraterone acetate and enzalutamide but were still inhibited by tubulin-binding drugs [15].…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations
“…Specifically, despite the limitations of non-randomized retrospective studies, the CAST [17] report was the first to investigate the outcomes of C followed by abiraterone acetate and vice versa in two groups of patients following progression while on D. In this study, the activity of C as a third-line therapy was found to be inferior compared with its use as a second-line therapy in the other group. It is likely that the presence of constitutively activated androgen receptor splice variants, which generally lack the carboxy-terminal ligand-binding domain, resulted in resistance to abiraterone acetate and enzalutamide but were still inhibited by tubulin-binding drugs [15].…”
Section: Discussionmentioning
confidence: 84%
“…The activity of C following abiraterone acetate has been investigated in five studies [15][16][17][18][19]. Specifically, despite the limitations of non-randomized retrospective studies, the CAST [17] report was the first to investigate the outcomes of C followed by abiraterone acetate and vice versa in two groups of patients following progression while on D. In this study, the activity of C as a third-line therapy was found to be inferior compared with its use as a second-line therapy in the other group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be a rationale for CAB treatment in the fourth-line. There is limited literature data with a small series of patients on current treatment with CAB beyond third-line therapies for CRPC, as shown in Table 3 [7,[16][17][18][19][20][21][22]. In third-or fourth-line CAB, the median PFS is reported around 4 months and most of the patients died within a year.…”
Section: Discussionmentioning
confidence: 99%